Toxicology case of the month: ingestion of two unidentified tablets by a toddler. Issue 9 (18th August 2006) - McCoubrie, D; Murray, L; Daly, F F S; Little, M
Abstract : An asymptomatic 18 month old child presents to the emergency department of a small district hospital shortly after ingesting two unidentified tablets. A small number of pharmaceuticals and illicit drugs may produce life threatening toxicity in a small child if ingested even in one or two dose units and the onset of toxicity may be delayed for some agents. Following risk assessment, a rational management plan is devised and the child is carefully monitored. The patient is observed overnight and discharged home the following day.